Bio design : nature, science, creativity - Myers, William; Antonelli, Paola (London : Thames & Hudson, 2012)
Designers and artists have always looked to nature for inspiration and materials, but only recently have they been able to alter and incorporate living organisms in their work. In a world with finite resources and a growing population, design that mimics or appropriates the sustainable template of nature is likely to prove as vital as it is novel. 'Bio Design' examines some seventy projects (concepts, prototypes and completed designs) that cover the fields of architecture, industrial processes, education, fine art, material engineering and bioengineering. Each project is illustrated by a short text, images and captions that combine to explain the problems the venture tackles, and how living materials and processes were harnessed to solve them in sustainable and aesthetically pleasing ways. Many of the solutions also provoke thought about manipulating life for human ends.
boek